DIPLOMASI INDONESIA TERHADAP SINGAPURA : UPAYA PENGEMBALIAN FUNGSI PENGAWASAN UDARA FLIGHT INFORMATION REGION (FIR) PERIODE 2012-2016 - Bagus Sandi Mahardhika, - (2019)
This research was conduct to know about Indonesia's diplomacy action in order to manage the air navigation system called Flight Information region (FIR) independently. Singapore held the rights to utilise FIR in Indonesia's teritory since 1946. Flight Information Region (FIR) itself is a part of regulation of aviation that control the area navigation system. This layed on the agreement between the Government of Indonesian Republic and Singaporean Government in 1995. Indonesia face the sovereignty challenge due to aviation range is beyond the nation's control as the ICAO said the aviation has no boundaries. In this case Indonesia's need to secure the sovereignty since the air has the strategic utility in national security. Indonesia take the diplomacy action to reclaim the FIR's right from Singapore and to settled this long time dispute. The purpose of this research is to analyse Indonesia take diplomacy effort in order to reclaim the Flight Information Region rights from Singapore in A,B, and C area. And also to know how the air navigation service impacting the nation's sovereignity. The research method is the qualitative-descriptive approach. All Indonesia's success and obstacles in negotiation with Singapore will be analyse with diplomacy theory, national interest, and sovereignty perspective. The result of this research is revealed that Indonesia unable to reclaim and control the Flight Information Region from Singapore. But the result from the last 3 years showed some positive feedback from Singapore. Realising this potential Indonesia will increasing the capability and set a target in 2023, The right of FIR Navigation service will be back to Indonesia.